DETERMINAN STRUKTUR MODAL PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI - Zara Tania Rahmadi; Muhammad Aria Wahyudi (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2021)
This research was conducted to determine the effect of liquidity and profitability on capital structure. The object of research is mining companies for 3 years from 2017-2019 totaling 44 companies with a sample of 13 companies. The analytical method used is panel data regression with SPSS 26 statistical test tool. The test results show that liquidity has no significant effect on capital structure and profitability has a significant effect on capital structure. Taken together, liquidity and profitability have a significant effect. It can be concluded that the optimal capital structure can be achieved if the proportion of debt and the level of capital can be adjusted by considering very minimal financial risk.